SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN KREDIT ANGGOTA KOPERASI KARYAWAN PT PELITA CENGKARENG PAPER MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Muhamad Harun (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
Abstract Employee cooperatives that are trusted to manage mandatory savings funds with the aim of prospering their members must be able to calculate the creditworthiness value without being subjective to minimize the possibility of bad credit risk. So a decision support system is needed using the Simple Additive Weighting (SAW) method with 5C analysis, namely Character, Capacity, Capital, Collateral and Conditional of Economy, which is the best solution to calculate quickly, precisely and accurately about the creditworthiness of cooperative members. So that there are no mistakes in decision making that result in bad credit and harm employee cooperatives.